Productivity and growth in Europe: Editor's introduction - Hubert Strauss (EIB Papers, 2011)
I summarize the main results and policy insights from the 2011 EIB Conference on Productivity and Long-Term Growth Potential in Europe. Europe's need for productivity growth has become more pressing against the backdrop of huge government debt and a beginning slowdown in labour supply. The contributors to the EIB Conference and this volume suggest that governments should embrace domestic and international competition by dismantling anticompetitive product market regulations, especially in services. Private and public R&D should feature high on the policy agenda, but their effectiveness should be enhanced by removing overly protective elements of the patent system. Education attainment and quality as well as life-long learning should be fostered and more emphasis put on an ICT-literate workforce. Productivity-enhancing resource reallocation may further require lower employment protection and stronger incentives for regional and sectoral mobility. Finally, Europe faces large broadband investment needs, calling for a predictable network regulation framework and targeted public support to broadband roll-out to less profitable areas.
Keywords: 330; Produktivität; Wirtschaftspotenzial; Produktivität; Deregulierung; Wettbewerbspolitik; Europäische Forschungs- und Technologiepolitik; Patentrecht; Binnenwanderung; EU-Staaten